α-Pinene: Docking Study, Cytotoxicity, Mechanism of Action, and Anti-Biofilm Effect against Candida albicans - Daniela Bomfim de Barros; Luanna de Oliveira e Lima; Larissa Alves da Silva; Mariana Cavalcante Fonseca; Rafael Carlos Ferreira; Hermes Diniz Neto; Danielle da Nóbrega Alves; Walicyranison Plinio da Silva Rocha; Luciana Scotti; Edeltrudes de Oliveira Lima; Marianna Vieira Sobral; Lúcio Roberto Cançado Castellano; et al. (Antibiotics, 2023)
Candida albicans is associated with serious infections in immunocompromised patients. Terpenes are natural-product derivatives, widely studied as antifungal alternatives. In a previous study reported by our group, the antifungal activity of α-pinene against C. albicans was verified; α-pinene presented an MIC between 128–512 µg/mL. In this study, we evaluate time-kill, a mechanism of action using in silico and in vitro tests, anti-biofilm activity against the Candida albicans, and toxicity against human cells (HaCaT). Results from the molecular-docking simulation demonstrated that thymidylate synthase (−52 kcal mol−1), and δ-14-sterol reductase (−44 kcal mol−1) presented the best interactions. Our in vitro results suggest that α-pinene’s antifungal activity involves binding to ergosterol in the cellular membrane. In the time-kill assay, the antifungal activity was not time-dependent, and also inhibited biofilm formation, while rupturing up to 88% of existing biofilm. It was non-cytotoxic to human keratinocytes. Our study supports α-pinene as a candidate to treat fungal infections caused by C. albicans.